2013
DOI: 10.1177/1094428113484970
|View full text |Cite
|
Sign up to set email alerts
|

Team Faultline Measures

Abstract: Team faultlines-hypothetical dividing lines based on member attributes that split a team into relatively homogeneous subgroups-influence team processes across contexts, as recent meta-analytic findings show. We review the available faultline measures with regard to their properties and identify several limitations, including dealing with more than two subgroups. We thus propose a new cluster-based approach, average silhouette width (ASW), that identifies the number of subgroups and subgroup membership. We then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(101 citation statements)
references
References 67 publications
(226 reference statements)
2
96
1
Order By: Relevance
“…Based on findings from organizational research on team diversity, we argue that the teacher's beliefs about the value of diversity in the classroom are an important contextual moderating factor for the relationship between pupils' intergroup contact and their tendencies to socially exclude others based on social categories. These assumptions are in line with research on faultlines, hypothetical dividing lines splitting groups into relatively homogeneous subgroups (e.g., Meyer & Glenz, 2013;Thatcher & Patel, 2011. Prior findings show that such splits between subgroups need not necessarily be detrimental in the presence of pro-diversity beliefs (Homan, van Knippenberg, van Kleef, & De Dreu, 2007).…”
supporting
confidence: 76%
“…Based on findings from organizational research on team diversity, we argue that the teacher's beliefs about the value of diversity in the classroom are an important contextual moderating factor for the relationship between pupils' intergroup contact and their tendencies to socially exclude others based on social categories. These assumptions are in line with research on faultlines, hypothetical dividing lines splitting groups into relatively homogeneous subgroups (e.g., Meyer & Glenz, 2013;Thatcher & Patel, 2011. Prior findings show that such splits between subgroups need not necessarily be detrimental in the presence of pro-diversity beliefs (Homan, van Knippenberg, van Kleef, & De Dreu, 2007).…”
supporting
confidence: 76%
“…Regression results revealed that there were no three-way interactions between status hierarchy steepness, task complexity, and mean status that significantly predicted team conflict or team performance (lowest B = −.07, p = .17 for the conflict types separately; B = −.05, p = .27 for the combined team conflict scale, and B = .06, p = .37 for team performance). In the second model, we tested whether our hypothesized relations would change when Meyer and Glenz's (2013) average silhouette width (ASW) faultline measure of status-based subgroups was added as a second moderator. We calculated this measure based on our status variable and a constant using the asw.cluster package in R. Yet, the three-way interactions between status hierarchy steepness, task complexity, and the ASW fault line measure did not significantly predict team conflict or team performance (lowest B = −.02, p = .81 for the conflict types separately; B = −.01, p = .86 for the combined team conflict scale, and B = .04, p = .70 for team performance).…”
Section: Notesmentioning
confidence: 99%
“…The effects of faultlines have been mainly attributed to self-categorization theory (Meyer & Glenz, 2013;Thatcher & Patel, 2012;Lau & Murnighan, 2005), which assumes that the salience of social categories depends on their normative fit (i.e., to the extent to which they are meaningful), their cognitive accessibility, and their comparative fit (Turner, Hogg, Oakes, Reicher, Wetherell, 1987). Comparative fit is the extent to which similarities and differences are perceived as a division into social categories: A target is perceived as different if it belongs to a rater's outgroup.…”
Section: Team Faultlinesmentioning
confidence: 99%
“…There are several ways of calculating faultline measures, but overall, the average silhouette width (ASW) measure (Meyer & Glenz, 2013) is the most robust and versatile method (Meyer & Glenz, 2013;Meyer et al, 2014). As none of the groups under investigation was larger than seven members, we restricted it to detecting two subgroups to restrict the number of isolates (i.e., subgroups of size 1).…”
Section: Faultline Strengthmentioning
confidence: 99%
See 1 more Smart Citation